Torrefaction of sewage sludge / A.R.M. Daud, M.R Mazli and N.A.C. Ahmad - M.Daud, A.R; Mazli, M.R; C.Ahmad, N.A (2018)
Torrefaction is a treatment which serves to improve the qualities of biomass in relation to thermochemical processing techniques for energy generation. In this study, the torrefaction of sewage sludge, was investigated in a furnace model MF! 06 at temperature ranging from 150 to 300°C, for torrefaction residence time varying from 5 to 60 min. the torrified sewage sludge product was studied to obtain the energy content and percentage yield.